Diagnostic value of repeated ice tests in the evaluation of ptosis in myasthenia gravis - Park, Jun Young (PLoS One, 2017)
Twenty-six patients with ptosis related to Myasthenia gravis (MG) and 38 controls with ptosis other than MG were included. All patients were tested with the ice test 2 times on separate days in the afternoon. The margin reflex distance (MRD) was measured before and immediately after 2-minute application of ice on the eyelids. The ice test was judged positive if there was an improvement of at least 2.0 mm of MRD after the ice test. Among the patients with negative test results, 'equivocal’ was defined by improvement of MRD from at least 1.0 mm to less than 2.0 mm after the ice test. Repeated ice test results showed an agreement of 61.5% in MG, and 97.4% in nonmyasthenic ptosis. Repeated ice tests increased the sensitivity by 34.6% compared to a single test. Among the patients with repeatedly negative test results, 63.6% of those who showed equivocal results at least once turned out to be MG. Of those with repeated non-equivocal negative results, nobody turned out to be MG. There was no significant difference of the ice test results between ocular MG and generalized MG (p = 0.562).